Heterochromatin decondesation in Creole cattle carrier of Robertsonian franslocation (rob 1; 29). Action of 5â€“azacytidineâ€“C Descondensación de la heterocromatina en bovinos criollos portadores de la translocación Robertsoniana (rob1; 29). Acción del inductor 5â€“azacitidinaâ€“C - Postiglioni Alicia; Iriarte Wanda; Iriarte Andrés; Llambí Silvia; De Soto Leticia; Artigas Rody; De Betancourth Miguel (Acta Agronómica)
The Robertsonian translocation (rob1; 29) is widely spread in commercial breeds and specially in genetic reserve of American Creole cattle. It is also described a delay on embryo development in front of normal ones. The action of 5–aza–C, as an hypomethylated agent, could permitted to decondensate the constitutive or facultative heterochromatin. In this work we made induction with the 5–aza–C(10mM, 2 hrs) analogs, in lymphocyte cultures of female and male carriers and normal Creole cattle. The DNA hypometilation is found in the inactive X chromosome of late replication as it is incorporated during the last hours of cell culture. The decondensing effects of 5–aza–C analogs is observed in multiple regions of the autosomes chromatin, the rob1; 29 and the BTA1. A correlation between hypometilated regions and decondensed of facultative (conditional) heterochromatin is related with genomic instability, and epigenetic reprogramming. La translocación Robertsoniana (rob1; 29) está ampliamente distribuida en razas comerciales y en reservas genéticas de bovinos Criollos americanos. Se ha descrito un enlentecimiento en el desarrollo de embriones portadores de esta aneuploidía, frente a embriones normales. La acción de la 5–aza–C, como agente desmetilante, permitiría descondensar la heterocromatina constitutiva o facultativa. En este trabajo se realiza inducción con el análogo de base 5–aza–C(10mM, 2 hrs) en cultivos linfocitarios de una hembra y un macho portadores de la rob1; 29, frente a bovinos Criollos normales. Se controla la acción desmetilante del inductor al identificar la despiralización del cromosoma X de replicación tardía en hembras y permitir el análisis de la despiralización de la cromatina en múltiples regiones de los autosomas (grandes, medianos, pequeños); de la rob1; 29 y del BTA1. Se discute la correlación existente entre regiones desmetiladas con la descondensación de la heterocromatina facultativa (condicional), relacionándola con la inestabilidad genómica, y la reprogramación epigenética.